Hydraulics and field performance of subsurface inline drip irrigation system - JUVANA MARY JOSEPH PRAVEEN JOHNSON SANJANA T. K; Er. Asha Joseph (Guide) (Tavanur 2006 Kelappaji College of Agricultural Engineering and Technology)
Effect of mulch in subsurface drip method of irrigation.susurface drip & fertigation. a comparative evaluation of conventional, surface drip & subsurface method of irrigation
Hydraulics and field performance of subsurface inline drip irrigation system